Reversing the Trend of Stunting in Sudan : Opportunities for Human Capital Development through Multisectoral Approaches - Touray, Sering; Etang Ndip, Alvin (World Bank, Washington, DC, 2021)
The report is structured as follows: section two provides an overview of the existing literature on undernutrition and its determinants. Section three describes the methodology used in this report, the UNICEF conceptual framework and the MICS data collected in 2010 and 2014. The analysis section (section four) begins by describing the nature of stunting among 0-5-year-old children in Sudan highlighting differences in stunting rates across states, households, gender, and age groups. This analysis is followed by an overview of the extent of inequalities in access to adequate levels of nutrition drivers among 0–23-month-old children. The second part of section four examines the extent to which access to adequate levels of nutrition drivers influences stunting in Sudan. The authors estimate marginal effects of access levels (including individual and joint access) on the probability of being stunted to identify the main nutrition drivers that significantly affect stunting and the heterogeneity of their effects across space, wealth, and gender. Finally, section five concludes by discussing the implications of the results on multisectoral responses to stunting in Sudan.